Aberrant epithelial membrane antigen expression in dermal cellular fi brous histiocytoma with central necrosis and epidermal ulceration a potential mimicker of epithelioid sarcoma. Issue 2 (2013) - Longo, F; Musumeci, G; Parenti, R; Vecchio, GM
No abstract available